Outcomes following acute nonvariceal upper gastrointestinal bleeding in relation to time to endoscopy: results from a nationwide study - Jairath, V.; Kahan, B. C.; Logan, R. F. A.; Hearnshaw, S. A.; Doré, C. J.; Travis, S. P. L.; Murphy, M. F.; Palmer, K. R. (Endoscopy, 2012)
Background and study aims: Despite the established efficacy of therapeutic endoscopy, the optimum timeframe for performing endoscopy in patients with nonvariceal upper gastrointestinal bleeding (NVUGIB) remains unclear. The aim of the current audit study was to examine the relationship between time to endoscopy and clinical outcomes in patients presenting with NVUGIB.Patients and methods: This study was a prospective national audit performed in 212 UK hospitals. Regression models examined the relationship between time to endoscopy and mortality, rebleeding, need for surgery, and length of hospital stay.Results: In 4478 patients, earlier endoscopy ( < 12 hours) was not associated with a lower mortality or need for surgery compared with later ( > 24 hours) endoscopy (odds ratio [OR] for mortality 0.98, 95 % confidence interval [CI] 0.88 – 1.09 for endoscopy > 24 hours vs. < 12 hours; P = 0.70). In patients receiving therapeutic endoscopy, there was a nonsignificant trend towards an increase in rebleeding associated with later endoscopy (OR 1.13, 95 %CI 0.97 – 1.32 for endoscopy > 24 hours vs. < 12 hours), with the converse seen in patients not requiring therapeutic endoscopy (OR 0.83, 95 %CI 0.73 – 0.95 for endoscopy > 24 hours vs. < 12 hours; interaction P = 0.003). Later endoscopy ( > 24 hours) was associated with an increase in risk-adjusted length of hospital stay (1.7 days longer, 95 %CI 1.39 – 1.99 vs. < 12 hours; P < 0.001).Conclusions: Earlier endoscopy was not associated with a reduction in mortality or need for surgery. However, it was associated with an increased efficiency of care and potentially improved control of hemorrhage in higher risk patients, supporting the routine use of early endoscopy unless specific contraindications exist. These results may help inform the debate about emergency endoscopy service provision.